TERJEMAHAN EKSPRESI PERMINTAAN (REQUEST EXPRESSION) DALAM PERCAKAPAN FILM THE LAST SONG - -, Sumardiono (Widya Wacana: Jurnal Ilmiah, 2013)
Abstract: This research aims at how request expressions are translated in film The Last Song. It was found that there were two kinds of request expression, namely direct and indirect request expression. For direct expression, three kinds of it were found; they are mood derivable, obligation statement and performative. While for the indirect one, they are suggestory formulae, query preparatory and mild hint. Generally the accuracy of translation for request expression is high which is related to the technique mostly applied, literal technique. Only some are not quite high. This case reflects the fact that the locution and illocution forces are generally the same in both languages. Keywords: Translation, Request Expression